Analisis Tingkat Kepuasan Agen PERISAI terhadap Regulasi BPJS Ketenagakerjaan (Studi Kasus pada Kantor Cabang Darmo Surabaya) - Amelia Cahya Syah Fitri; Nurhadi Nurhadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research analyzes the satisfaction level of PERISAI agents regarding BPJS Ketenagakerjaan regulations at the Darmo Surabaya Branch Office. The PERISAI program, launched in 2018, represents a strategic innovation in the agency system to expand membership, particularly in the Non-Wage Recipient (BPU) sector. The study employs a qualitative approach with a case study design, involving participatory observation over four months (September-December 2024), in-depth interviews, and documentation analysis. Results indicate that the PERISAI policy transformation since May 2022, particularly the increase in contribution incentives from 7.5% to 15%, has positively impacted agent motivation. The reward system combining financial and non-financial incentives through gathering programs and point systems proves effective in building loyalty. Success in achieving BPU participant acquisition targets is influenced by agents' ability to develop personal approaches and build local community networks. The integration of digital platforms in acquisition processes and performance monitoring enhances operational efficiency. Capacity development programs through cross-generational communication training and social security fund management provide a strong foundation for PERISAI agents' task execution.